Using an emissive uridine analogue for assembling fluorescent HIV-1 TAR constructs - Srivatsan, Seergazhi G. (2007)
Emissive nucleoside analogues that are sensitive to their microenvironment can serve as probes for exploring RNA folding and recognition. We have previously described the synthesis of an environmentally sensitive furan-containing uridine and its triphosphate, and have demonstrated that T7 RNA polymerase recognizes this modified ribonucleoside triphosphate as a substrate in in vitro transcription reactions. Here we report the enzymatic preparation of fluorescently tagged HIV-1 TAR constructs and study their interactions with a Tat peptide. Two extreme labeling protocols are examined, where either all native uridine residues are replaced with the corresponding modified fluorescent analogue, or only key residues are site-specifically modified. For the HIV-1 Tat–TAR system, labeling all native uridine residues resulted in relatively small changes in emission upon increasing concentrations of the Tat peptide. In contrast, when the two bulge U residues were site-specifically labeled, a reasonable fluorescence response was observed upon Tat titration. The scope and limitations of such fluorescently tagged RNA systems are discussed.